OPTIMALISASI PELAYANAN PUBLIK DESA MELALUI PENINGKATAN KOMPETENSI APARATUR PEMERINTAHAN DESA - Muh Askal Basir; La Asiri (INCIDENTAL : Journal Of Community Service and Empowerment, 2026)
This Community Service Program aimed to enhance the competence of village government officials to optimize the quality of public services. The program was implemented through socialization, training, mentoring, and evaluation using pre-test and post-test assessments. The training materials covered public service standards, village administrative management, records management, service communication, and the utilization of information technology. The results demonstrated a significant improvement in the competence of village officials, with the average score increasing from 48% to 87%. This improvement contributed to better public service quality, as reflected in greater service timeliness, information transparency, officials’ responsiveness, and higher community satisfaction. Furthermore, the program strengthened village governance by improving the professionalism, effectiveness, and accountability of public officials. Therefore, training and mentoring proved to be effective strategies for developing the capacity of village officials in delivering high-quality, responsive, and community-oriented public services.